Evolution of smart devices and human movement apps: Recommendations for use in sports science education and practice - Keogh, J. W. L.; Espinosa, H. G.; Grigg, J. (Journal of Fitness Research, 2016)
Many smart phones and tablets possess high-speed cameras. An increasing number of human movement professionals (e.g. personal trainers, athletics coaches, strength and conditioning coaches and physiotherapists) are beginning to use human movement analysis apps with their smart phones/tablets to quantitatively assess their clients` performance and injury risk. However, an understanding of the validity and reliability of these tools is required. This narrative review seeks to list some relevant human movement apps; summarise the validity and reliability of selected apps and to provide recommendations for their use in education and practice.